Partisipasi Petani Dalam Pemanfaatan Getah Pinus di Hutan Lindung Soputan Melalui Program Hutan Kemasyarakatan (Studi Kasus Pada Kelompok Tani Rin Pamu di Desa Tombasian Atas Kecamatan Kawangkoan Barat Kabupaten Minahasa) - Malvry I. Lombok; Hengki D. Walangitan; Maria Y.M.A. Sumakud (COCOS, 2021)
ABSTRACTThis study aims to describe the level of participation and analyze the factors that influence the level ofparticipation of Rin Pamu farmer groups in community forestry, especially the use of pine resin. This study uses asurvey method with a closed questionnaire model. Determination of respondents using saturated sampling techniquewith the number of respondents as many as 34 people. Determination of the level of participation using a Likertscale. Furthermore, to analyze the relationship of respondents socioeconomic factors to the level of participationusing Chi Square analysis. The results showed that the level of participation of farmer groups at the planning stagewas moderate. Furthermore, at the stage of implementation and monitoring the evaluation is quite high. The factorsthat influence the level of participation are age and education, while the income factors does not affect the level ofparticipation of farmer groups in the HKm program, especially the use of pine resinin the Mount Soputan ProtectionForest.Keywords: Participation, Pine Sap, Rin Pamu Farmer Group